Modelling of leaching process of rare earth element Praseodymium (Pr) - N. I. S., Ramle; Wan Hanisah, Wan Ibrahim; A., Hisham (2018)
Rare earth elements have their unique physical and chemical properties character that makes them important elements in several of high-tech application. It’s very important to ensure the efficient separation of REE is carried out optimally. In order to achieve this, understanding the fundamental process is essential. Thus the purpose of this study is to relate how the leaching process occurs by using shrinking core model for a better understanding. Rare earth separation process usually passed through a cascade of physical processing steps including beneficiation process. After filtration, leaching solution is passed through a sequence of solvent extraction process with several mixer-settler steps to separate individual or mixed rare earths compounds. The aims of this work are to study and develop a model for leaching process of rare earth elements, Praseodymium (Pr). It was conducted for the purpose of the recovery of the rare earth element from ore. The mathematical model of this work was developed based on the shrinking core model (SCM). The effect of temperature ranging from 30oC – 80oC and concentration (1.5 mol/L – 3 mol/L) of the reagent was carried out in this work. The developed model from this work can be used to predict the recovery of Praseodymium (Pr) from the solid liquid leaching process which can be a good reference for future research.